Rodzaje aukcji na wytwarzanie energii elektrycznej z odnawialnych źródeł energii w świetle przepisów ustawy o odnawialnych źródłach energii - Kosiński, Eryk; Trupkiewicz, Marcin (Studia Prawa Publicznego, 2019)
After an analysis of certain legal texts, the authors have established that under Polish law the President of the Energy Regulatory Offi ce may conduct 56 diff erent types of auctions for generators of the electric energy from renewable sources (RSE). For each individual RSE installation complying with the RES parameters a separate auction may be carried. One RSE installation may take part in several RSE auctions provided it satisﬁ es the parameters of each individual installation. These parameters concern both the premises connected with the start-up process (the commencement of the production of electric energy) of a given installation and the premises of technical nature such as carbon dioxide emission or the level of the installation capacity used, as well as premises of a subjective character regarding individual producers participating in the auction. A detailed analysis of all types of RSE auctions described in the Act of 20 February 2015 on renewable sources of energy allows to determine which types of installation may take part in individual actions. However, of key importance from the point of view of the possibility of a RSE auction to be carried are secondary regulations which allow the Council of Ministers to determine individual types of RSE auctions in which the volume of energy, subject of the auction, will be made available. Consequently the Council of Ministers which runs the State policy within the area of RSE has become essentially responsible not only for the possibility of conducting an RSE auction, but also for the implementation of the EU climate and energy policy which is also binding upon Poland.